Kredit Bermasalah, Kecukupan Modal dan Profitabilitas Pada Bank BUMN Yang Terdaftar Di Bursa Efek Indonesia - Rizka Ulandari (BJRM (Bongaya Journal of Research in Management), 2023)
Organization and management is producced by history, social reality and location, so individual group, and srtuctural influenc to en organizational behavior. A s historical production that an organization continually avaluate in problematic of human being at any events in valve to social situation and organization location.The key of succesful organization is a human recources management such as work hard, creativity, and quality minded. So an organization peformance management in third millenium era needs knowledge and understanding management which involve to enviromental changes of bussiness for reacting accarately. Many firm reform the bussiness strategy whit market base oriented and evaluate intensively of the internal bussieness competency.The increation needs for exellent quality and performance can we see on empericial supportings at UK Cooperaive Bank, SIA, Baxter Int’l, SQC Indonesia, New BRI etc.